A cyclometalating organic ligand with an Iridium center toward dramatically improved photovoltaic performance in organic solar cells. Issue 18 (11th February 2019) - Wu, Qingjing; Cheng, Yang; Xue, Zhongyuan; Gao, Xuyu; Wang, Menghan; Yuan, Wenbo; Huettner, Sven; Wan, Shigang; Cao, Xudong; Tao, Youtian; Huang, Wei
Abstract : An organometallic Ir complex exhibited enhanced photovoltaic performance compared to an organic ligand. Abstract : Organometallic compounds as photoactive materials are relatively new in organic solar cells. Upon cyclometalation, the octahedral heteroleptic Ir complex TBzIr exhibits significantly enhanced optical-absorption and improved film-morphology compared to the planar organic 2-(5′′-hexyl-[2, 2′:5′, 2′′-terthiophen]-5-yl)benzo[ d ]thiazole (TBz) ligand. Thus, a dramatically improved power conversion efficiency (PCE) from ∼0 to 3.81% is attained when combined with PC71 BM.